Low-temperature solution-processed memory transistors based on zinc oxide nanoparticles - Faber, Hendrik; Burkhardt, Martin; Jedaa, Abdesselam; Kälblein, D.; Klauk, Hagen; Halik, Marcus (Advanced Materials, 2009)
We report on thin!film transistors based on ZnO nanoparticles processed from solution and with a maximum temperature of 100 °C. Electron mobilities up to 2.5 cm²V−1s−1 are obtained, and top-gate TFTs show non-volatile memory properties with a large, stable hysteresis and a memory ratio of 105. Memory TFTs operate in ambient, have good shelf-life (>6 months), and useful endurance properties.